Industrial, managemental, and company-size determinants of tax avoidance in the coal mining sector - Febiansyah, Egi Saputra; Stiawan , Hari (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This study aims to determine whether there is an influence of institutional ownership, independent managerial ownership and company size on tax avoidance in coal sub-sector mining companies listed on the Indonesia Stock Exchange for the period 2017-2022. This study uses quantitative descriptives. The sampling technique used is purposive sampling with a total sample obtained of 8 companies within 6 years so that 48 samples were obtained after the criteria data were taken. The analysis used is panel data analysis using Eviews 9 software. The results of the analysis test state that the variables of institutional ownership, independent managerial ownership, and company size have an influence on tax avoidance simultaneously. Partial testing states that the variables of institutional ownership and independent managerial ownership do not have a positive effect on tax avoidance, while company size affects tax avoidance